3.2 Can Neurobiological Subgroups in Psychotic Illness Advantage Drug DISCOVERY? - Tamminga, Carol (Schizophr Bull, 2017)
Background: Are there neurobiological subgroups in schizophrenia or across psychotic illnesses that will select individuals who will respond to drugs that enhance parvalbumin (PV)-positive inhibitory interneuron function? The question requires not only clarification and validation of biomarker-based schizophrenia subgrouping options but also specific models around how to fit these with the pathology of PV-positive inhibitory neuronal dysfunction. Methods: Recent studies have proposed approaches for defining neurobiologically distinct psychosis groups. The Bipolar Schizophrenia Network for Intermediate Phenotypes study collected a large group of probands with psychosis, their relatives, and healthy controls for precise diagnosis, clinical characterization, and a deep phenotyping study in 5 sites across the United States. Using the resultant biomarkers (including cognitive, electrophysiological [EEG], motor, and imaging biomarkers), hypothesis-free statistical clustering analyses were carried out, using only biomarker data to cluster the probands on biologically based characteristics rather than by clinical symptoms. Results: These analyses resulted in outcomes showing neurobiologically compelling, biomarker-based clusters of psychotic probands called Biotypes. The psychosis Biotypes were distinguished by several characteristics including the extent of cognitive dysfunction, specific EEG profiles, and characteristic regional anatomy, all in a relatively distinctive profile. Each Biotype had predominant clinical characteristics but without a distinction in psychosis. Conclusion: There are several biomarker characteristics that could plausibly be associated with dysfunctional neocortical cell firing patterns in schizophrenia. And these distinctive neocortical firing patterns could relate to underlying pathology in PV-positive interneurons, especially if the cellular dysfunction was prominent enough to cause cognitive dysfunction. It is plausible that a biomarker characteristic in psychosis could function as a drug target, normalizing with drug action, and associating with a therapeutic response, like cognitive improvement, a process that would greatly advantage drug discovery. Although this approach is in early phases in psychiatric disorders such as schizophrenia, it is implemented in other disorders in medicine, where cellular targets for drug development are common.